Modeling of plasma accumulation, heating and confinement in a source of thermonuclear neutrons - Lavrent’ev, O.A.; Maslov, V.A.; Germanova, S.V.; Shevchuk, B.A.; Krutko, N.A. (Вопросы атомной науки и техники, 2006)
The mathematical model and computer program were prepared for modeling of physical processes in a source of thermonuclear neutrons. As a result of modeling, the time dependences on characteristics of system were obtained for plasma parameters in starting conditions, for the conditions to approach to a stationary mode, for the plasma parameters in stationary mode and for neutron yield.